Evaluation of infections in orthopedic patients using next-generation sequencing. Issue 11 (November 2021) - Ogawa, Shinya; Chikumi, Hiroki; Tanishima, Shinji; Hayashi, Ikuta; Mihara, Tokumitsu; Nagashima, Hideki
Abstract: Introduction: Culture tests are used to diagnose infections, but there are various problems such as low sensitivity in detecting infections in orthopedic cases. To address this problem, next generation sequencing (NGS) analysis, which can comprehensively search for bacterial genes, is being applied clinically. In this study, we examined whether NGS analysis was useful in evaluating infections in orthopedic cases. Methods: The participants were 23 patients suspected of having an infection between 2016 and 2017. Samples were collected from tissues suspected of being infected and were subjected to culture tests and NGS analysis, and the positive rates from the culture tests and from the NGS analysis were compared. We also attempted to determine cutoff value for the NGS analysis. Results: A total of 20 cases were ultimately diagnosed as infections and 3 cases were diagnosed as non-infections. The sensitivity of the culture tests was 70%, and the sensitivity of the NGS analysis was 55%. When the NGS analysis was performed with the diversity index set to the cut-off value, the sensitivity was 75% for the Simpson index. In this study, the sensitivity was 90% when the analysis was performed using the NGS index, which is a combination of the diversity index and the OTUs (operational taxonomic units) value. Conclusion: NGS analysis using the NGS index showed excellent sensitivity and specificity compared to culture tests. NGS analysis is therefore a useful modality for assessing infections in orthopedic cases.